Nitrogen and harvest effects on soil properties under rainfed switchgrass and no‐till corn over 9 years: implications for soil quality. Issue 2 (15th January 2014) - Stewart, Catherine E.; Follett, Ronald F.; Pruessner, Elizabeth G.; Varvel, Gary E.; Vogel, Kenneth P.; Mitchell, Robert B.
Abstract Nitrogen fertilizer and harvest management will alter soils under bioenergy crop production and the long‐term effects of harvest timing and residue removal remain relatively unknown. Compared to no‐tilled corn (NT‐C, Zea mays L.), switchgrass (Panicum virgatum L.) is predicted to improve soil properties [i.e. soil organic C (SOC), soil microbial biomass (SMB‐C), and soil aggregation] due to its perennial nature and deep‐rooted growth form, but few explicit field comparisons exist. We assessed soil properties over 9 years for a rainfed study of N fertilizer rate (0, 60, 120, and 180 kg N ha−1) and harvest management on switchgrass (harvested in August and postfrost) and NT‐C (with and without 50% stover removal) in eastern NE. We measured SOC, aggregate stability, SMB‐C, bulk density (BD), pH, P and K in the top 0–30 cm. Both NT‐C and switchgrass increased SMB‐C, SOC content, and aggregate stability over the 9 years, reflecting improvement from previous conventional management. However, the soils under switchgrass had double the percent aggregate stability, 1.3 times more microbial biomass, and a 5–8% decrease in bulk density in the 0–5 and 5–10 cm depths compared to NT‐C. After 9 years, cumulative decrease in available P was significantly greater beneath NT‐C (−24.0 kg P ha−1) compared to switchgrass (−5.4 kg P ha−1). When all measured soil parameters were included in the Soil Management Assessment Framework (SMAF), switchgrass improved soil quality index over time (ΔSQI) in all depths. NT‐C without residue removal did not affect ΔSQI, but 50% residue removal decreased ΔSQI (0–30 cm) due to reduced aggregate stability and SMB‐C. Even with best‐management practices such as NT, corn stover removal will have to be carefully managed to prevent soil degradation. Long‐term N and harvest management studies that include biological, chemical, and physical soil measurements are necessary to accurately assess bioenergy impacts on soils.